An Investigation of an Expanded Police Chaplaincy Model: Police Chaplains' Communications with Local Citizens in Crisis. (September 2016) - Gouse, Valerie
Many people look to public servants such as the police to provide emotional and social support in addition to their traditional responsibilities of protecting citizens from harm and danger. Consequently, various police departments around the country are partnering with qualified community religious leaders to comfort and counsel local citizens in times of crisis. This qualitative study examines how police chaplains interact with local citizens in crisis, focusing on communication as it relates to the chaplains' ministry of presence and listening behaviors. The analysis of content generated from focus groups and in-depth interviews with police chaplains reveals that the mere presence of chaplains diffuses difficult situations as citizens seem to find solace being in the company of these non-threatening, non-judgmental crisis clergy. Further analysis shows that chaplains engage in verbal-person centeredness and nonverbal immediacy, two specific behaviors that have been found to constitute supportive listening.